Perspektif Pendidikan Al-Zarnuji dan Relevansinya dengan Kurikulum Merdeka Belajar - Heri Dermawan; Maragustam Siregar (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2024)
Education is oriented toward science, skills, and values. This study aims to present the Al-Zarnuji education perspective and its relevance to the independent curriculum of learning. The method of research used is the method of library study which is to find and analyze various sources related to dialogues, journals, and texts related to speech. The primary data source of this research is the Ta’lim Muta’alim book by Imam AL-Zarnuji. The secondary data is the relevant kemendikbud curriculum document. It was found that the educational thinking of Imam Al-Zarnuji with an independent curriculum is an educational perspective that explains curricula, educational purposes, educators, pupils, and methods of learning according to Imam Al-Zarnuji relevance with the curriculums of independent learning applied today.